Continuous diamond-carbon nanotube foams as rapid heat conduction channels in composite phase change materials based on the stable hierarchical structure. (1st November 2020) - Hu, Naixiu; Li, Haichao; Wei, Qiuping; Zhou, Kechao; Zhu, Wei; Zhang, Long; Li, Songbo; Ye, Wentao; Jiao, Zengkai; Luo, Jingting; Ma, Li; Yan, Qingwei; et al.
Abstract: Phase change materials with considerable heat effect during phase change have been regarded as one of the most promising candidates for latent thermal energy storage and thermal management. Although intensive efforts have been dedicated to the high-efficiency application, challenges remain in enhancing the thermal response due to their intrinsically low thermal conductivity. Here, continuous diamond-carbon nanotube foams are designed and fabricated as thermal conductive reinforcement. The unique diamond foam with extremely high thermal conductivity act as the "main channel" for thermal flow transportation, and the directly-grown, well-distributed carbon nanotube networks plays role of the "second heat channel". Benefiting from this stable hierarchical structure, thermal conductivity of the phase change composite has been enhanced to 9.72 W m −1 K −1 from 0.105 W m −1 K −1 of paraffin matrix, representing one of the highest enhancement ever-reported. Besides this conceptual advance, we discover that the hybrid structure considerably suppresses subcooling, a common problem that causes a much lower crystallization temperature than the melting temperature of many phase change materials. The special design promises to be one of the most efficient solutions for thermal response promotion of phase change materials and their extensive application. Graphical abstract: Image 1 Highlights: A continuous hierarchical thermal conductive reinforcement based on diamond and directly-grown carbon nanotubes was proposed and developed. Thermal conductivity and heat charging rate of the composites were markedly promoted. Good phase change reversibility and thermal stability were achieved.